Investigate and compare the effect of one session wrestling training on elite wrestlers dehydration, hematocrit and blood electrolytes in the morning and evening. - Habibi, A.; Nikbakht, M.; Shakerian, S.; Ketabi, S. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume II: Bio-Mechanics and Sports Engineering., 2008)
Finding the best time in day time for activity and competitions with reduction of factors of performance block and health is very important and vivid. So the purpose this research was Investigate and compares the effect of one session interval wrestling training On elite wrestlers Dehydration, Hematocrit and blood electrolytes in the morning and evening in Khuzestan. This research done hy the use of semi practical research plan consists of two practical and control group, with pre and post test. Sample includes 12 elite wrestlers who had the qualifications as practical group and also 12 non athletics people as control group. Interval protocol training on practical group in the evening and morning like skill sample athletes with 50% maximal heart rate in duration of 10 minutes as wrestling warm up and then with 80% maximal heart rate continued to 20 minutes as wrestling training and finally with 60% maximal heart rate was done in recovery and cooling in 10 minutes. The data was analyzed after normalization by paired t-test in meaningful level (p<=0.05) the result of difference of changes between morning and evening tests showed that more dehydration in the evening in compare with morning has occurred (p=0.000), and amount of Hematocrit in the morning was much more reduced than the evening(p=0.017). Density sodium and potassium yon did not exist meaningful changes in the morning and evening test (p=0.687) (p=0.165). With attention to other research about circadian rhythm probably dehydration in evening than morning was effect of increase of body temperature in evening.